2022
DOI: 10.1038/s41598-022-26050-z
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of rumen microbiome in sika deer (Cervus nippon yakushimae) from unique subtropical ecosystem in Yakushima Island, Japan

Abstract: Yaku sika deer (Cervus nippon yakushimae) are endemic to Yakushima Island, whose landscape covered with primary evergreen forest is recognized as a World Heritage Site. In this study, the rumen bacterial microbiota (RBM) of wild Yaku sika was characterized using high throughput sequencing of bacterial 16S rRNA genes combined with targeted cultivation and functional analyses. Comparative analyses of RBM datasets from other ruminant animals revealed distinct community structure among domesticated and wild rumina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 62 publications
1
0
0
Order By: Relevance
“…Similarly, Oscillospiraceae UCG-005 is positively correlated with isobutyrate production (64). The above taxa have also been identified in similar proportions in other members of the genus Cervus including C. nippon (sika deer) and C. elaphus (red deer) (65)(66)(67)(68)(69). Therefore, the composition of the elk fecal microbiota in this study corroborates previous analyses of North American elk and other ruminants.…”
Section: General Observations Of the Elk Fecal And Vaginal Microbiotasupporting
confidence: 87%
“…Similarly, Oscillospiraceae UCG-005 is positively correlated with isobutyrate production (64). The above taxa have also been identified in similar proportions in other members of the genus Cervus including C. nippon (sika deer) and C. elaphus (red deer) (65)(66)(67)(68)(69). Therefore, the composition of the elk fecal microbiota in this study corroborates previous analyses of North American elk and other ruminants.…”
Section: General Observations Of the Elk Fecal And Vaginal Microbiotasupporting
confidence: 87%
“…In the present study, we examined the rumen microbiota using 16S rRNA sequencing analysis. As previously elucidated and documented in Sika deer [42], we observed that the predominant bacteria belonged to the phyla Firmicutes and Bacteroidota, with a high relative ratio of Firmicutes to Bacteroidetes in this study. This occurrence may be attributed to the fact that Sika deer typically inhabit cold and high-altitude regions [43], where a high ratio of Firmicutes to Bacteroidetes is advantageous for fat deposition, helping animals adapt to severe cold cli-mates [44], thereby enhancing their resilience to these challenging conditions.…”
Section: Effect Of Dfpe On Bacteria Communities In Vitrosupporting
confidence: 82%